HUMAN RESOURCE MANAGEMENT (HRM) IN IMPROVING CUSTOMER BEHAVIOR THROUGH EMOTIONAL ATTACHMENT (EA) - Putri, Dinda Febrianti; Agus R, Abu Hasan; Wahid Zaini, Abdul; Manshur, Umar; Khaer, Abu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore and analyze the implementation of Human Resource Management (HRM) strategies in improving customer behavior through Emotional Attachment (EA) in educational institutions. The focus of this research is to identify key elements in HRM strategies that positively influence emotional interactions between educational institutions and their consumers. Qualitative research methods were used by combining interviews and observation. Data analysis will include identifying patterns, themes, and nuances that emerge from interviews and observations. This research will illustrate how HRM policies in educational institutions, such as teaching staff development and cultural atmosphere, can shape students' emotional attachment. The output will provide an in-depth understanding of the influence of HRM on students' emotional experiences and its potential to improve student behavior in educational settings. The results of this research show that Human Resource Management (HRM) in improving customer behavior through Emotional Attachment (EA) has a significant role in influencing the emotional relationship between employees and customers, which ultimately improves customer behavior. Through developing employee skills and leadership, empowering staff, as well as measuring and monitoring employee satisfaction, it can be said to be a key component in creating a work environment that supports Emotional Attachment. HRM strategies that are responsive to employee needs open the door to more positive personal interactions, creating strong emotional bonds between employees and customers